Strategy Analysis of ZISWAF Fund Management Using SWOT: Case Study of Mosque in Mimika - Irnawan, Roni; Amrizal, Amrizal (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research aims to 1) Analyze the extent of the strengths, weaknesses, opportunities, and challenges for the management of ZISWAF funds of the Mosque in Mimika. 2) Identify appropriate strategies in the management of ZISWAF funds of the Mosque in Mimika. This research focuses on events that occur in mosques and uses qualitative techniques. This type of research uses a qualitative approach with descriptive qualitative research methods. Data was collected through filling out questionnaires and interviews with respondents related to the mosque and analyzing related documents. Based on the results of the study, the management of ZISWAF funds in the mosque in Mimika, on internal factors at the strength point shows the importance of managing Ziswaf funds for the prosperity of the mosque and the community, but the weakness is the human resources of mosque managers who are less effective in carrying out the mandate so that it has an impact on the development of mosque facilities and the management of limited ziswaf funds. On external factors, the Opportunities point shows the positive response of the community regarding the activities of the Mosque and the support of religious leaders and the local government in religious activities made by the Mosque, while the Threats are the many religions that have developed so that Conflicts related to religious interests in Mimika Regency are easy to occur.